Value of Bidders Default Risk Information: Designing Reliable Auction Using Post-Bidding Mechanism - Chatterjee, Anirban; Mukherjee, Subhadip (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2025)
Traditional auction theory typically assumes that bidders will fully honor their commitments upon winning. However, this assumption often proves inadequate in high-stakes auctions, such as those for infrastructure projects or luxury assets, where securing the necessary funds post-auction can pose challenges. Factors such as market volatility, liquidity constraints, or delays in financing frequently result in bidder defaults, leading to substantial disruptions for sellers, including the costs of re-auctioning and project delays. This paper seeks to bridge this gap in auction theory by exploring how comprehensive information about bidders’ default risks can be utilized through a straightforward post-bidding mechanism. Furthermore, it highlights the advantages this approach offers to the auctioneer compared to scenarios where such critical information is unavailable.